EFL LEARNERS’ ABILITY OF DEFINITE AND INDEFINITE ARTICLES: A STUDY OF FIRST-YEAR ENGLISH EDUCATION STUDENTS IN INDONESIA - Risza Dwiputri; Riyen Permata (Universitas Mahaputra Muhammad Yamin, 2025)
EFL learners in Indonesia have learned to use English articles since they started learning English. However, English articles pose significant challenges for Indonesian EFL learners due to the absence of articles in Bahasa Indonesia, abstract and complex usage rules, and overgeneralization and transfer errors. This study examines the ability of first-year EFL learners in the English Education Department at UMMY Solok (academic year 2024/2025) in using definite and indefinite articles. Using a descriptive quantitative design, 10 first-year students from English Education Department at UMMY Solok were assessed by using a validated 40-item grammar test. Although the sample was limited, the study offers preliminary insights since it was an exploratory or early stage research. The results revealed that the students’ proficiency level in using both definite and indefinite articles were at good level. The findings suggest that students have a functional understanding of the basic usage of articles. Students likely demonstrate awareness of noun classification and contextual usage, which are key to article use. This study contributes to curriculum development by highlighting the importance of gradual, context-based instruction in teaching English articles. Furthermore, it recommends that future researches should examine article usage in students’ academic writing across genres or proficiency levels.